Synthesis and Pharmacological Characterization of New Photocaged Agonists for Histamine H3 and H4 Receptors - Yang Zheng; Meichun Gao; Maikel Wijtmans; Henry F. Vischer; Rob Leurs (MDPI AG, 2024)
The modulation of biological processes with light-sensitive chemical probes promises precise temporal and spatial control. Yet, the design and synthesis of suitable probes is a challenge for medicinal chemists. This article introduces a photocaging strategy designed to modulate the pharmacology of histamine H3 receptors (H3R) and H4 receptors (H4R). Employing the photoremovable group BODIPY as the caging entity for two agonist scaffolds-immepip and 4-methylhistamine-for H3R and H4R, respectively, we synthesized two BODIPY-caged compounds, 5 (VUF25657) and 6 (VUF25678), demonstrating 10-100-fold reduction in affinity for their respective receptors. Notably, the caged H3R agonist, VUF25657, exhibits approximately a 100-fold reduction in functional activity. The photo-uncaging of VUF25657 at 560 nm resulted in the release of immepip, thereby restoring binding affinity and potency in functional assays. This approach presents a promising method to achieve optical control of H3R receptor pharmacology.